Benzannulation of arynes with dimethylacetonedicarboxylates via an insertion-fragmentation-Dieckman-aromatization cascade: Expeditious entry to naphthoresorcinols and binaphthoresorcinols. Issue 21 (24th May 2019) - Singh, Shweta; Samineni, Ramesh; Pabbaraja, Srihari; Mehta, Goverdhan
Abstract: Aryne insertions into 1, 3, 5-tricarbonyl bearing dimethylacetonedicarboxylate (DMAD) proceeds through a 4-step cascade process to eventuate in a versatile one pot synthesis of functionally embellished naphthoresorcinols. Functional group amplifications and transformations on these entities have been explored with the intent to apply them for natural products syntheses and to access other interesting scaffolds. Graphical abstract: Image 1